Overcoming barriers to guideline implementation: the case of cardiac rehabilitation. Issue 6 (27th June 2010) - Fernandez, R S; Davidson, P; Griffiths, R; Salamonson, Y
Abstract : Aims: This study explored the strategies used by cardiac rehabilitation (CR) coordinators to overcome the obstacles to implementation of the evidence-based Reducing Risk in Heart Disease guidelines. Methods: The study design used qualitative, semistructured in-depth interviews with 20 CR coordinators from New South Wales, Australia, to explore the strategies used to facilitate guideline implementation. Non-probability sampling was used to recruit CR coordinators to obtain a broad understanding of the issues. Interviews were transcribed and thematic content analysis was undertaken to identify common themes. Results: Coordinators addressed the barriers to implementing guidelines through their commitment to best practice and striving to overcome the odds through providing opportunistic health education, alternate methods of secondary prevention, and partnering and engaging with local communities. Conclusions: Although CR coordinators face multiple barriers to implementing evidence-based guidelines for patients with coronary heart disease, they use strategies such as harnessing community capacity and using available resources creatively. The development of a more integrated, multifactorial and coordinated approach to improving use of guidelines in clinical practice to improve the treatment and secondary prevention of coronary heart disease is urgently needed.